2016
DOI: 10.1007/s00062-016-0553-9
|View full text |Cite
|
Sign up to set email alerts
|

Management of Unruptured Saccular Aneurysms of the M1 Segment with Flow Diversion

Abstract: Flow diversion can be used to treat small, unruptured aneurysms of the M1 segment of the MCA and even though side vessel occlusion can occur clinically relevant infarction occurs infrequently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Thus, more than one-quarter of aneurysms were located outside traditional locations, which mirrors a trend in the literature on flow diversion that advocates its use further distal in the cerebrovascular tree at or beyond the circle of Willis. [10][11][12] While approximately onequarter of aneurysms in the EuFRED were large and giant and deemed too difficult to treat using traditional endovascular techniques, the median aneurysm diameter of 7.6 mm is a testament that flow diversion may be suitable for aneurysms traditionally managed with coil embolization with or without assist devices such as stents or balloons. 13 Along those lines are also the results of a matched analysis comparing flow diversion with coiling of small and uncomplicated aneurysms, demonstrating a potential benefit for the flow diverter even in simple lesions.…”
Section: Aneurysm Characteristics In Eufredmentioning
confidence: 99%
“…Thus, more than one-quarter of aneurysms were located outside traditional locations, which mirrors a trend in the literature on flow diversion that advocates its use further distal in the cerebrovascular tree at or beyond the circle of Willis. [10][11][12] While approximately onequarter of aneurysms in the EuFRED were large and giant and deemed too difficult to treat using traditional endovascular techniques, the median aneurysm diameter of 7.6 mm is a testament that flow diversion may be suitable for aneurysms traditionally managed with coil embolization with or without assist devices such as stents or balloons. 13 Along those lines are also the results of a matched analysis comparing flow diversion with coiling of small and uncomplicated aneurysms, demonstrating a potential benefit for the flow diverter even in simple lesions.…”
Section: Aneurysm Characteristics In Eufredmentioning
confidence: 99%
“…Overall, previous series have reported a rate of complete/near-complete occlusion between 60% and 90% after flow-diversion treatment of MCA aneurysms. [5][6][7][8][9][12][13][14]20 The paucity of large and prospective studies, the heterogeneity of the reported populations, and the relatively short follow-up periods can explain this variation. Our study, the largest to date, demonstrated that the overall rate of complete/near-complete occlusion is roughly 80% during a mean follow-up of 14 months.…”
Section: Angiographic Outcomes Of Mca Aneurysms After Flow Diversionmentioning
confidence: 99%
“…1 Recently, flow diversion has been used as an alternative technique for complex wide-neck MCA aneurysms, incorporating Ն1 side branch or in cases of previous endovascular or surgical failure. [5][6][7][8][9][10][11][12][13][14] However, the role of flow diversion in this location is controversial, and the efficacy and safety of this technique remain unclear. We performed a systematic review and meta-analysis of all published series examining flow diversions for the treatment of MCA aneurysms with the aim of clarifying the following: 1) aneurysm occlusion rate, 2) treatment-related complications and clinical outcome, and 3) the fate of the MCA side branch covered with the device.…”
mentioning
confidence: 99%
“…The early use of flow diversion was centered on the treatment of aneurysms arising from the internal carotid artery (ICA) with 79/108 (73.1%) aneurysms treated in the PUFS study arising from either the cavernous or ophthalmic segments of the ICA and the majority of the aneurysms being between 10 and 25 mm in size (78.7%). Since the publication of this K p48MW pivotal trial, numerous reports on the use of flow diversion distal to the circle of Willis have been published [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Ravindran et al [26] recently reported their multicohort study of FDS use distal to the circle of Willis defined as at or beyond the A1, M1 and P1 segments of the ACA, MCA and PCA, respectively.…”
Section: Discussionmentioning
confidence: 99%